Effect of harvest date on the dormancy period of yam (Dioscorea rotundata) - Swannell, M.C.; Wheeler, T.R.; Asiedu, Robert; Craufurd, Peter Q. (Wiley, 2003)
Tuber dormancy enables yams to survive in the ground during the dry season and post‐harvest storage. Three clones of Dioscorea rotundata were harvested after five intervals and then stored in a cooler (20.6°C) or at ambient temperature (27.8°C). The time from harvest to sprouting was shorter as harvest was delayed. The period from sowing to sprouting for each clone was similar for tubers harvested from 140 days after planting, but tubers harvested earlier took longer to sprout. The cooler temperature delayed sprouting. Tubers of two clones sprouted after only 70 days of crop growth. If the dormancy period of these young tubers can be broken, the generation time of yam crop improvement programmes could be considerably reduced.